Perbaikan Proses Bisnis Menggunakan Metode Business Process Improvement (BPI) (Studi Kasus Pada Bagian Pelaksana Urusan Logistik UTD Palang Merah Indonesia (PMI) Kota Malang) - Ibnu Irawan Pratama; Djoko Pramono; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The logistics management department is part of the administration section of the Malang City UTD PMI. In UTD PMI Malang City there are sections that are formed to help achieve organizational goals. In the implementation of medical logistics, there are 5 main business processes, namely the receipt of medical logistics goods, purchase of medical logistics goods> Rp. 5,000,000, purchase of medical logistics goods <Rp. 5,000,000, delivery of medical logistics items (for internal), and delivery of goods medical logistics (for external). The implementation of business processes in this section is still often a constraint, namely the execution of time that has exceeded a predetermined time. This study uses a five whys analysis method to determine the root causes of each business process. The results of the analysis in general, the root of the problem is about recording documents that are still using paper which can cause an increase in the organization's expenditure to buy paper and the risk of being lost. Based on the results of the evaluation carried out treatment by using streamlining tools provided by Business Process Improvement (BPI) to make business process recommendations. From the results of the business process recommendations made then a simulation is conducted to see the improvement of each business process. on the business process of delivering medical logistics (for external) goods by 1 hour 41 minutes with a percentage increase of 24.9%.